Ketersediaan SDM Dan Sarana Prasarana Dalam Menunjang Pembelajaran Al-Qur’an di Pondok Pesantren Hamalatul Qur’an Putri Jogoroto Jombang - Waslah Waslah; Abd Kholid; Indah Tiarawati (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2022)
Education is formal and non-formal programmed learning experiences. Therefore, Currently, the Indonesian government continues to seek various ways so that learning can continue and develop during the COVID-19 pandemic, both learning innovations, procurement of supporting infrastructure, teaching methods and much more. In this case the Islamic boarding school is one of the non-formal education functions to complement the abilities of students by providing learning experiences that are not obtained in school education. Hamalatul Qur'an Islamic Boarding School in its learning prioritizes learning the Qur'an. The learning process is packaged with tahfidz pesantren, namely: recitation of the wethon, depositing the Qur'an to a ustadz or cleric, madrasahtul diniyah, memorizing the Qur'an quickly and so on. This study aims to determine the suitability of the availability of human resources as well as facilities and infrastructure in supporting teaching and learning activities at the Hamalatul Qur'an Islamic boarding school. The study used a descriptive qualitative approach. The data collection methods were observation, interviews and document collection during the study. The results of the study were to determine: the role of HR and Sarpras, how strategic, as well as the supporting and inhibiting factors in the learning process to memorize the Al-Quran at the Hamatul Quran Islamic Boarding School.